2016
DOI: 10.1021/acsami.6b08901
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Overoxidized Polypyrrole Films with Orderly Structure as High-Performance Anodes for Li- and Na-Ion Batteries

Abstract: Flexible polypyrrole (PPy) films with highly ordered structures were fabricated by a novel vapor phase polymerization (VPP) process and used as the anode material in lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs). The PPy films demonstrate excellent rate performance and cycling stability. At a charge/discharge rate of 1 C, the reversible capacities of the PPy film anode reach 284.9 and 177.4 mAh g in LIBs and SIBs, respectively. Even at a charge/discharge rate of 20 C, the reversible capacity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 56 publications
1
43
0
Order By: Relevance
“…The low initial Coulombic efficiency can be attributed to irreversible reaction, which is a common phenomenon of anode materials for LIBs and could be mitigated by some prelithiation processes . Figure c shows the rate performance of PTTE‐based LIBs, PTTE can deliver specific capacitance of 973 mA h g −1 at a current density of 100 mA g −1 , which is much higher than that of most reported organic anode materials, such as Li 4 C 8 H 4 O 4 nanosheets (232 mA h g −1 at 24.1 mA g −1 ), CMP from porphyrin with 4‐thiophenephenyl groups (TThPP) (666 mA h g −1 at 200 mA g −1 ), poly(bithiophene)/carbon (PBT/C) composite (650 mA h g −1 at 320 mA g −1 ), PDCzBT (404 mA h g −1 at 100 mA g −1 ) and the ordered polypyrrole film (285 mA h g −1 at 300 mA g −1 ) . The high specific capacity of PTTE might be attributed to its high surface area and inherent homogeneous microporous structure, endowing PTTE with abundant active sites for Li ion storage.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The low initial Coulombic efficiency can be attributed to irreversible reaction, which is a common phenomenon of anode materials for LIBs and could be mitigated by some prelithiation processes . Figure c shows the rate performance of PTTE‐based LIBs, PTTE can deliver specific capacitance of 973 mA h g −1 at a current density of 100 mA g −1 , which is much higher than that of most reported organic anode materials, such as Li 4 C 8 H 4 O 4 nanosheets (232 mA h g −1 at 24.1 mA g −1 ), CMP from porphyrin with 4‐thiophenephenyl groups (TThPP) (666 mA h g −1 at 200 mA g −1 ), poly(bithiophene)/carbon (PBT/C) composite (650 mA h g −1 at 320 mA g −1 ), PDCzBT (404 mA h g −1 at 100 mA g −1 ) and the ordered polypyrrole film (285 mA h g −1 at 300 mA g −1 ) . The high specific capacity of PTTE might be attributed to its high surface area and inherent homogeneous microporous structure, endowing PTTE with abundant active sites for Li ion storage.…”
Section: Resultsmentioning
confidence: 96%
“…[49,50] Figure 2c shows the rate performance of PTTE-based LIBs, PTTE can deliver specific capacitance of 973 mA h g −1 at a current density of 100 mA g −1 , which is much higher than that of most reported organic anode materials, such as Li 4 C 8 H 4 O 4 nanosheets (232 mA h g −1 at 24.1 mA g −1 ), [47] CMP from porphyrin with 4-thiophenephenyl groups (TThPP) (666 mA h g −1 at 200 mA g −1 ), [51] poly(bithiophene)/carbon (PBT/C) composite (650 mA h g −1 at 320 mA g −1 ), [52] PDCzBT (404 mA h g −1 at 100 mA g −1 ) [27] and the ordered polypyrrole film (285 mA h g −1 at 300 mA g −1 ). [53] The high specific capacity of PTTE might be attributed to its high surface area and inherent homogeneous microporous structure, endowing PTTE with abundant active sites for Li ion storage. In addition, PTTE shows a low the lowest unoccupied molecular orbital level of −3.59 eV ( Figure S4, Supporting Information), which facilitates the electron injection into the polymer chains, [54,55] leading to a complete lithiation reaction to thiophene units of PTTE.…”
Section: Electrochemical Performance Of Ptte For LI + Storagementioning
confidence: 99%
“…(h) SEM micrograph of CuO nanorod array on Cu foil [133] . (i) Schematic illustration of Na-ions storage mechanism in polypyrrole film [127] .…”
Section: Flexible Anode Materials With Carbon Matrix For Sibsmentioning
confidence: 99%
“…Polymeric film can be used as a promising flexible anode material for SIB. Yuan et al [127] have demonstrated polypyrrole film as a potential flexible anode material for SIB. It was prepared via vapor phase polymerization method (Table S1aj) bonds.…”
Section: Flexible Anode Materials Without Carbon Matrix For Sibsmentioning
confidence: 99%
“…In this article, polypyrrole is chosen for the inner layer due to its facile and scalable synthesis, electric conductivity, low gas permeability and support for ORR/OER. [16,17,18,19,20] It should be noted that PPy-based membranes have been applied in Li-air batteries by Cui et al to promote oxygen diffusion into the cathode on the air side using a tubular architecture. [21] PPy/ carbon nanocomposite has been applied as a cathode in a hybrid Li-air battery, and it has been clearly demonstrated to support ORR with sufficiently high electrocatalytic activity.…”
Section: Design Considerationsmentioning
confidence: 99%